Formulasi Nugget untuk Mencegah Anemia pada Remaja Putri Berdasar Menu Pondok Pesantren - Pradini, Viska Amalia; Kristianto, Yohanes; Hikmah, Nurul (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2023)
Background : Anemia is a health problem in the world, both in developed and developing countries, which is not only experienced by pregnant women and women of childbearing age (WUS) but can also be experienced by adolescents, both young men and young women. Based on the 2013 Riskesdas, the prevalence of anemia in Indonesia was 21.7%, with 26.4% of sufferers aged 5-14 years and 15-24 aged 18.4% with a prevalence of anemia in women of 23.7%. One of the efforts to prevent anemia in young women can be done by consuming foods that are high in protein, iron and vitamin C. Purpose : The research aims to find out the right formulation of nuggets made from shrimp, tofu, sorghum flour and green spinach, product organoleptic namely color, aroma, taste and texture, analyzing macronutrients (protein, fat and carbohydrates) and micronutrients (iron and Vitamin C). Methods : The study used a completely randomized design with four formulas namely F1, F2, F3 and F4, based on the comparison of shrimp, tofu, sorghum flour and green spinach, 10:20:30:40; 40:30:20:10; 25:20:15:10; and 10:15:20:25. Statistical analysis used the Kruskall Wallish test and follow-up tests used the Mann-Whitney test. Results : The results of the study based on the RDA of 30% of female adolescents showed that 100 g of F1 formula contained protein, fat, carbohydrates, iron and vitamin C, namely 45%, 41%, 22%, 51% and 37%. Formula F2 contains 48%, 42%, 19%, 51% and 55%. Formula F3 contains 50%, 41%, 15%, 50% and 74%. Formula F4 contains 52%, 40%, 12%, 49% and 93%. Conclusion : The formula chosen based on the best treatment level is F2 with the first ranking result on the organoleptic test variable is taste.